MENINGKATKAN TATA CARA BERWUDHU’ PADA ANAK TUNAGRAHITA RINGAN - Yulianis - - (Universitas Negeri Padang, 2012)
Against the background of this research by the findings in the field there are three students Tunagrahita mild and one teacher in the classroom SLB Perwari DV in Padang. In the learning procedure for wudoo ', teachers still tend to use the conventional approach that is still a teacher center teacher means more dominant as the transfer of knowledge in children, so children get bored easily accept an explanation from the teacher. Based on the researchers tried to use the method of study tours to improve procedures for wudoo 'is done by utilizing the water faucet mosque, it is intended that the child can clearly see the procedure for doing wudoo' well on the water faucet mosque. This study uses action research methods class (Classroom Action Research) conducted in collaboration with colleagues. Data were collected through observation techniques, tests and interviews, then analyzed qualitatively and quantitatively.